2019
DOI: 10.3390/ijerph16122170
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity and Anthropometric Status of Mother–Child Pairs from Enset (False Banana) Staple Areas: A Panel Evidence from Southern Ethiopia

Abstract: Background: A sizable cross-sectional studies demonstrated a low dietary diversity in Southern Ethiopia. However, its seasonal trend has not been well studied in areas where nutrient-poor enset (false banana (Ensete ventricosum)) foods are major staple. Moreover, there is scarcity of information on seasonal nature of anthropometric status of mother–child pairs (MCP) from the same areas in Southern Ethiopia. Therefore, the present study aimed to investigate the dietary diversity and anthropometric status of MCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 33 publications
(48 reference statements)
1
38
0
Order By: Relevance
“…The intake of animal source food and fruits were low, and this is similar to findings from other developing countries (Bosha et al 2019;Campbell et al 2014;Hirvonen, Taffesse, and Worku Hassen 2016). However, we found a high intake of carbohydrate source foods which indicates the monotonous nature of the diet (Table 6).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The intake of animal source food and fruits were low, and this is similar to findings from other developing countries (Bosha et al 2019;Campbell et al 2014;Hirvonen, Taffesse, and Worku Hassen 2016). However, we found a high intake of carbohydrate source foods which indicates the monotonous nature of the diet (Table 6).…”
Section: Discussionsupporting
confidence: 90%
“…Some studies show that there are differences in wasting prevalence rates between the dry and wet seasons (Kinyoki et al 2016) and between post-harvest and pre-harvest seasons (Roba et al 2016). Earlier research from Sidama, where the current study was done showed seasonal wasting where nutrient-poor enset (Ensete ventricosum) is the major staple crop (Abebe et al 2006;Bosha et al 2019;Ferro-Luzzi et al 2001). These studies were from the more fertile area of Sidama than the current study which was carried out in a drought-prone population, and also showed that children and adults both suffered from exposure to seasonal energy stress.…”
Section: Introductionmentioning
confidence: 75%
“…Shebedino and Hula are two of nineteen districts and two city administrations of the zone [27]. Nearly 99% of the households in the five kebeles (kebele is the smallest administrative unit of a district) sampled from the two districts produced enset in the l2 months before the survey [28].…”
Section: Methodsmentioning
confidence: 99%
“…On top of this, the design effect of 1.5 was considered, and 10% of the basic sample size was added to compensate for those lost to follow-up, resulting in a total of 510. However, a total of 625 mothers with 24–59-month-old children were enrolled at the beginning in order to obtain a sufficient sample size for additional analysis [28]. Nonetheless, 578 completed the study, while the rest left for different reasons: death (1), delivery (4), and sickness or moving to other places (42).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation